Speech Genre Motivating Story As A SemiCultural Phenomenon - Pardaeva Dilfuza Raimovna; Shodmonova Feruza Boris kizi (Euro Asian Journal Publishing, 2025)
This article examines the motivational story as a special speech genre that functions at the intersection of communication, pedagogy and culture. The author analyzes the structural features of motivational stories, their pragmatic focus and semi-cultural nature. The study is based on the approaches of discourse analysis and linguacultural studies, emphasizing the role of motivational stories in the formation of behavioral models and value attitudes of the individual.
Keywords: Motivational story; speech genre; semi-cultural phenomenon